SYNTHESIS AND CHARACTERIZATION OF GOLD NANOPARTICLES USING TEAK LEAF EXTRACT Tectona grandis (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2019)
Teak leaf extract has been successfully used in the synthesis of gold nanoparticles. It is characterized by a color change of the solution from yellow to red wine after the addition of teak leaf extract to HAuCl4 and the resulting wavelengths in the range of 500-600 nm that indicates that gold nanoparticles have been formed. Growth and stability of the gold nanoparticles produced using UV-Vis Spectroscopy. During observation during 144 hours the stability of gold nanoparticles after 48 hours with a wavelength of about 567.5 -568 nm.
Keywords: Gold Nanoparticles; Synthesis; Teak leaf; Spectroscopy UV-Vis